Hydrogen adsorption on calcium-decorated planar aluminene using density functional theory. Issue 1 (March 2020) - Bayasen, D S; Villagracia, A R; Pedrosa, G R; Lin, H; Ong, H L; David, M; Arboleda, N
Abstract: With the rising demand for clean energy, the concept of hydrogen economy has grown more popular, and with this popularity the need for better hydrogen storage materials increases. Decorated surface materials such as planar hexagonal aluminene are being studied to determine their potential as good hydrogen storage materials. This study theoretically investigates hydrogen adsorption on aluminene decorated with calcium, where calcium is binded on the top, bridge and hollow sites of aluminene using density functional theory. Results on decoration adsorption have shown that calcium can easily bind a distance of 1.80 Å to 2.80 Å on the top, bridge and hollow sites with binding energies of 1.85 eV, 2.01 eV, and 3.32 eV, respectively. The density of states of the calcium-decorated surface show that its electronic property is generally maintained with zero magnetization. Small amount of charges were adsorbed from the aluminium atoms to the calcium atom based on the charge difference. This leads to hydrogen molecule adsorption with low adsorption energies ranging from 34.13 meV to 80.51 meV. In addition, minimal broadening of energy levels were shown by the density of states. With these results, it can be concluded that planar hexagonal aluminene with low concentration of calcium atoms may lower the hydrogen capacity of aluminene.